2015
DOI: 10.1007/s13193-015-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of [18F] Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (FDG PET/CT) in the Initial Staging and Response Assessment of Locally Advanced Breast Cancer Patients Receiving Neoadjuvant Chemotherapy

Abstract: In India up to 50 % of breast cancer patients still present as locally advanced breast cancer (LABC). The conventional methods of metastatic work up include physical examination, bone scan, chest & abdominal imaging, and biochemical tests. It is likely that the conventional staging underestimates the extent of initial spread and there is a need for more sophisticated staging procedure. The PET/CT can detect extra-axillary and occult distant metastases and also aid in predicting response to chemotherapy at an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thirty-two studies assessing imaging modalities [anatomic: chest radiography, liver ultrasonography, chestabdomen-pelvis computed tomography (ct); metabolic: integrated positron-emission tomography (pet)/ct, integrated pet/magnetic resonance imaging (mri), bone scintigraphy] for staging in women with newly diagnosed bca and reporting the outcomes of interest were retained: one systematic review 12 , fourteen prospective cohort studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26] , and seventeen retrospective studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . The study population comprised women with all presentations of bca (including locally advanced bca 14,15,17,20,21,26 , inflammatory bca 21 , and invasive lobular and ductal carcinoma 35 ) and a mixed population of newly diagnosed bca. All studies reported data about the overall prevalence of asymptomatic distant metastases and the prevalence of metastases by site and by stage of disease at the time of initial diagnosis.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-two studies assessing imaging modalities [anatomic: chest radiography, liver ultrasonography, chestabdomen-pelvis computed tomography (ct); metabolic: integrated positron-emission tomography (pet)/ct, integrated pet/magnetic resonance imaging (mri), bone scintigraphy] for staging in women with newly diagnosed bca and reporting the outcomes of interest were retained: one systematic review 12 , fourteen prospective cohort studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26] , and seventeen retrospective studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . The study population comprised women with all presentations of bca (including locally advanced bca 14,15,17,20,21,26 , inflammatory bca 21 , and invasive lobular and ductal carcinoma 35 ) and a mixed population of newly diagnosed bca. All studies reported data about the overall prevalence of asymptomatic distant metastases and the prevalence of metastases by site and by stage of disease at the time of initial diagnosis.…”
Section: Literature Searchmentioning
confidence: 99%
“…The reference standard was considered on the basis of clinical and short-term follow-up imaging of metastatic lesions, or on the judgment of a multidisciplinary tumour board when biopsy or histopathology was not feasible, or both, because no "gold standard" for the detection of real metastases has been established. Fifteen studies did not provide enough information to determine whether the results of the reference standard test were blinded to the results of the index test 15,17,19,20,23,26,[30][31][32]34,[38][39][40][41]43 , and the risk for bias is related to the potential influence of previous knowledge on test interpretation 44 .…”
Section: Primary Literaturementioning
confidence: 99%
See 1 more Smart Citation